A Nomogram to Predict Long-Term Survival Outcomes of Patients Who Undergo Pneumonectomy for Non-small Cell Lung Cancer With Stage I-IIIB - Wu, Lei-Lei; Chen, Wu-Tao; Liu, Xuan; Jiang, Wen-Mei; Huang, Yang-Yu; Lin, Peng; Long, Hao; Zhang, Lan-Jun; Ma, Guo-Wei (Frontiers in Surgery, 2021)
BACKGROUND: In this study, we aim to establish a nomogram to predict the prognosis of non-small cell lung cancer (NSCLC) patients with stage I-IIIB disease after pneumonectomy. METHODS: Patients selected from the Surveillance, Epidemiology, and End Results (SEER, N=2,373) database were divided into two cohorts, namely a training cohort (SEER-T, N=1,196) and an internal validation cohort (SEER-V, N=1,177). Two cohorts were dichotomized into low- and high-risk subgroups by the optimal risk prognostic score (PS). The model was validated by indices of concordance (C-index) and calibration plots. Kaplan-Meier analysis and the log-rank tests were used to compare survival curves between the groups. The primary observational endpoint was cancer-specific survival (CSS). RESULTS: The nomogram comprised six factors as independent prognostic indictors; it significantly distinguished between low- and high-risk groups (all P<0.05). The unadjusted 5-year CSS rates of high-risk and low-risk groups were 33% and 60% (SEER-T), 34% and 55% (SEER-V), respectively; the C-index of this nomogram in predicting CSS was higher than that in the 8th TNM staging system (SEER-T, 0.629 vs. 0.584, P<0.001; SEER-V, 0.609 vs. 0.576, P<0.001). In addition, the PS might be a significant negative indictor on CSS of patients with white patients [unadjusted hazard ration (HR) 1.008, P<0.001], black patients (unadjusted HR 1.007, P<0.001), and Asian or Pacific Islander (unadjusted HR 1.008, P=0.008). In cases with squamous cell carcinoma (unadjusted HR 1.008, P<0.001) or adenocarcinoma (unadjusted HR 1.008, P<0.001), PS also might be a significant risk factor. CONCLUSIONS: For post pneumonectomy NSCLC patients, the nomogram may predict their survival with acceptable accuracy and further distinguish high-risk patients from low-risk patients.